Positive Allosteric Modulation of Alpha7 Nicotinic Acetylcholine Receptors Transiently Improves Memory but Aggravates Inflammation in LPS-Treated Mice - Lykhmus, Olena; Kalashnyk, Olena; Uspenska, Kateryna; Skok, Maryna (Frontiers in Aging Neuroscience, 2020)
Neuroinflammation accompanies or even precedes the development of cognitive changes in many brain pathologies including Alzheimer’s disease. Therefore, dampening inflammatory reactions within the brain is a promising strategy to support cognitive functions in elderly people and to prevent the development of neurodegenerative disorders. Nicotinic acetylcholine receptors containing α7 subunits (α7 nAChRs) are involved in regulating cell survival, inflammation and memory. The idea of our study was to evaluate the efficiency of α7-specific therapy at different stages of inflammation and to compare the effects of orthosteric agonist PNU282987 and type 2 positive allosteric modulator PNU120596 in mice after a single injection of lipopolysaccharide (LPS). The data presented demonstrate that PNU282987 protected mice from LPS-induced impairment of episodic memory by decreasing IL-6 levels in the blood, stabilizing the brain mitochondria and up-regulating the brain α7-, α3- and α4-containing nAChRs. Such treatment was efficient when given simultaneously with LPS or a week after LPS injection and was not efficient if LPS had been injected two months before. PNU120596 also decreased IL-6, stabilized mitochondria and up-regulated the brain nAChRs. However, its memory-improving effect was transient and disappeared after the end of injections cycle. Moreover, cessation of PNU120596 treatment resulted in sharp increase of IL-1β and IL-6 levels in the blood. It is concluded that activating α7 nAChRs protects mouse brain from pathogenic LPS effect at early stages of inflammation and is not efficient when irreversible changes have already occurred. The use of positive allosteric modulator does not improve the effect of agonist, possibly, potentiates the effect of endogenous agonist and results in non-desirable effects after treatment cessation.